Determinants of Inflation in Nepal - Gautam, Subas (Academia Research Journal, 2023)
By establishing a monetary and financial environment in which markets may operate without being concerned about irregular changes in the purchasing power of money, long-term economic growth can be achieved. The major goals of this study were to look at the inflation fluctuations in Nepal, to display the weighted structure of the CPI there, and to investigate the factors that affect inflation. The stationarity of the time series data was examined using the ADF test, and the cointegration between the variables was examined using the Engle-Granger test. The OLS method was used to estimate the long-run model. For the model's short run dynamism, the ECM model was also used. Throughout the research years, the inflation tendency has experienced significant swings. . Inflation peaked at 132.8 million in the fiscal year 1920, and it peaked at 4.1 in the fiscal year 1975. The ADF test result reveals that all variables become stationary only after the first difference, or I (1), for all variables utilized in this investigation. The long run OLS model is free from spurious regression, according to the Engle-Granger cointegration test, which shows that variables are cointegrated. The long-run OLS model demonstrates that government spending and Indian inflation have a positive and considerable impact on Nepalese inflation. For instance, an increase of 1% in the Indian consumer price index, government spending, and the currency rate results in increases of 0.70, 0.12, and 0.16 percent in the NCPI, respectively. According to the results of the ECM model, government spending and the Indian consumer price index have a positive and considerable impact on the consumer price index in Nepal in the short term. When government spending and the Indian consumer price index both grow by 1%, the corresponding increases in Nepal's consumer price index are 0.69 and 0.13 percent, respectively. While in the near term, the exchange rate has little impact on the consumer price index for Nepal. The NCPI and other explanatory variables are convergent into long-run equilibrium, according to the coefficient of ECM (-1), which is negative and significant at the 1% level.